Efektivitas Intervensi Lenina (Lung Function Evaluation and Nursing Intervention for Non-Pharmacological Asthma Management) terhadap Kemampuan Pengendalian Asma Pada Balita - Nurani, Lenina; Mendrofa, Fery Agusman Motuho; Iswanti, Dwi Indah (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Asthma is a chronic inflammatory disease of the respiratory tract with increasing prevalence in toddlers. Inadequate asthma control can lead to decreased quality of life, activity limitations, and increased risk of hospitalization. The LENINA (Lung function Evaluation and Nursing Intervention for Non-pharmacological Asthma management) intervention was designed as a comprehensive non-pharmacological approach to improve asthma control abilities. To analyze the effectiveness of LENINA intervention on asthma control abilities in toddlers, including lung function, frequency of asthma attacks, and family asthma management abilities. A quasi-experimental study with pretest-posttest with control group design was conducted on 42 toddlers with asthma in the working area of Nagrak Health Center, Cianjur Regency. The sample was divided into an intervention group (n=21) receiving LENINA intervention and a control group (n=21) receiving standard care. Lung function was measured using Peak Expiratory Flow Rate (PEFR), frequency of asthma attacks using observation sheets, and family asthma management abilities using questionnaires. Data were analyzed using paired t-test and independent t-test. LENINA intervention significantly improved PEFR values (p=0.000), decreased the frequency of asthma attacks (p=0.000), and increased family asthma management abilities (p=0.000) in the intervention group compared to the control group. The difference in PEFR value improvement in the intervention group (13.38) was greater than the control group (2.76). The decrease in asthma attack frequency in the intervention group (2.53 times/month) was more significant than the control group (0.38 times/month). The increase in family asthma management ability scores in the intervention group (20.67) was much greater than the control group (2.14). LENINA intervention proved effective in improving asthma control abilities in toddlers through improved lung function, decreased frequency of asthma attacks, and increased family asthma management abilities. The results recommend implementing LENINA intervention in asthma control programs for toddlers in primary healthcare facilities. Keywords: Toddler Asthma, Non-Pharmacological Intervention, LENINA, Asthma Control, Family Role.   ABSTRAK Asma merupakan penyakit inflamasi kronis pada saluran pernapasan yang prevalensinya terus meningkat pada balita. Pengendalian asma yang tidak adekuat dapat menyebabkan penurunan kualitas hidup, keterbatasan aktivitas, dan peningkatan risiko rawat inap. Intervensi LENINA (Lung function Evaluation and Nursing Intervention for Non-pharmacological Asthma management) dirancang sebagai pendekatan non-farmakologis komprehensif untuk meningkatkan kemampuan pengendalian asma. Menganalisis efektivitas intervensi LENINA terhadap kemampuan pengendalian asma pada balita yang meliputi fungsi paru, frekuensi serangan asma, dan kemampuan manajemen asma keluarga. Penelitian quasi-eksperimental dengan desain pretest-posttest with control group dilakukan pada 42 balita dengan asma di wilayah kerja Puskesmas Nagrak, Kabupaten Cianjur. Sampel dibagi menjadi kelompok intervensi (n=21) yang menerima intervensi LENINA dan kelompok kontrol (n=21) yang menerima perawatan standar. Pengukuran fungsi paru menggunakan Peak Expiratory Flow Rate (PEFR), frekuensi serangan asma menggunakan lembar observasi, dan kemampuan manajemen asma keluarga menggunakan kuesioner. Data dianalisis menggunakan uji paired t-test dan independent t-test. Intervensi LENINA secara signifikan meningkatkan nilai PEFR (p=0,000), menurunkan frekuensi serangan asma (p=0,000), dan meningkatkan kemampuan manajemen asma keluarga (p=0,000) pada kelompok intervensi dibandingkan kelompok kontrol. Selisih peningkatan nilai PEFR pada kelompok intervensi (13,38) lebih besar dibandingkan kelompok kontrol (2,76). Penurunan frekuensi serangan asma pada kelompok intervensi (2,53 kali/bulan) lebih signifikan dibandingkan kelompok kontrol (0,38 kali/bulan). Peningkatan skor kemampuan manajemen asma keluarga pada kelompok intervensi (20,67) jauh lebih besar dibandingkan kelompok kontrol (2,14). Intervensi LENINA terbukti efektif meningkatkan kemampuan pengendalian asma pada balita melalui peningkatan fungsi paru, penurunan frekuensi serangan asma, dan peningkatan kemampuan manajemen asma keluarga. Hasil penelitian ini merekomendasikan implementasi intervensi LENINA dalam program pengendalian asma pada balita di fasilitas kesehatan primer. Kata Kunci: Asma Balita, Intervensi Non-Farmakologis, LENINA, Pengendalian Asma, Peran Keluarga.